1984
DOI: 10.1111/j.1470-6431.1984.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Household and Child Care Task Responsibility of Spouses in Houston, Texas

Abstract: What are the differences in household and child care task responsibility by the employment role responsibility of spouses? What are the differences in the relationships between task preference, quality of task performance, and sex‐role ideology and household and child care task responsibility of spouses by the employment role responsibility of the spouses? What are the most important variables in determining household and child care responsibility? Data were collected from a random sample of wives and husbands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The relationship between sex role orientation and participation of the wife in household production has been mixed across the studies. Wheeler andArvey (1981), andRoss (1987) found that the wife's attitude did not significantly affect the division of household production. In contrast, Bird et ale (1984) found that sex role orientation had an effect on the management of family activities such as organizing social activities and planning family recreation, or financial management such as paying bills and balancing the checkbook.…”
Section: Educationmentioning
confidence: 98%
See 3 more Smart Citations
“…The relationship between sex role orientation and participation of the wife in household production has been mixed across the studies. Wheeler andArvey (1981), andRoss (1987) found that the wife's attitude did not significantly affect the division of household production. In contrast, Bird et ale (1984) found that sex role orientation had an effect on the management of family activities such as organizing social activities and planning family recreation, or financial management such as paying bills and balancing the checkbook.…”
Section: Educationmentioning
confidence: 98%
“…These activities are termed: "household production" (Reid, 1934;Schram & Hafstrom, 1984;Walker & Woods, 1976);"household work" {Bryant, 1983;Dolan & Scannell, 1987;Lovingood & Firebaugh, 1978;Matsushima, 1981;Meiners & Olson, 1987;Rowland et al, 1986;Sanik, 1981;Sanik & Mauldin, 1986;Walker, 1970); "housework" (Berardo et al, 1987;Coverman & Sheley, 1986;Glazer-Malbin, 1976;Hafstrom & Schram, 1983;Keith & Schafer, 1986;Model, 1981;Nickols & Metzen, 1978Rexroat & Shehan, 1987;Schooler et al, 1984;Schram & Hafstrom, 1986;Vanek, 1974); and "household tasks" (Hall & Schroeder, 1970;Hedges & Barnett, 1972;Shelton, 1990;Wheeler, 1984). In addition to the diversity of terms, the terms themselves and the categories included in them are also defined differently, depending on the purpose of the study.…”
Section: Definition Of Household Productionmentioning
confidence: 99%
See 2 more Smart Citations